The hbpA gene of Haemophilus influenzae type b encodes a heme-binding lipoprotein conserved among heme-dependent Haemophilus species. - Hanson, M S (1992)
A membrane-associated lipoprotein of Haemophilus influenzae type b has previously been shown to bind heme in vitro and to promote binding of this compound by Escherichia coli recombinants expressing this protein. The H. influenzae type b heme-binding protein A (HbpA) was found to be highly conserved with respect to both antigenicity and apparent molecular weight among heme-requiring Haemophilus species pathogenic for humans. To further the characterization of the structure and function of HbpA, the complete nucleotide sequence of its gene, hbpA, was determined. Analysis of the nucleotide sequence revealed a single large open reading frame of 1,638 bp encoding a protein of 546 amino acid residues, with a molecular weight of 60,695. The sequence of the amino-terminal end of this protein contained a potential site for lipid acylation and for cleavage by signal peptidase II, consistent with earlier biochemical evidence which indicated that HbpA is a lipoprotein. A search of GenBank for proteins with amino acid sequence similarity to HbpA revealed that the periplasmic dipeptide transport protein of E. coli, DppA, has 53% sequence identity to HbpA.